Digital Financial Literacy and Its Impact on Financial Behavior among Nepalese Youth - Khatri, Chudamani (Kalika Journal of Multidisciplinary Research, 2025)
Digital financial literacy empowers Nepalese youth by enhancing and improving digital knowledge, experience, awareness, and skills, ultimately improving their overall financial behavior. The main purpose of this study was to assess the impact of digital financial literacy dimensions on the financial behavior of the Nepalese youth. The study applied a correlational research design. A non- probablity sampling was used to select a total of 403 Nepalese youth. Data were collected by using a five-point Likert-scale survey questionnaire. The cross-sectional data were analyzed using IBM SPSS 20 and Smart-PLS 4.0. This study employed different statistical methods for data assessment, including reliability analysis, descriptive statistics, correlation analysis, and structural equation modeling (SEM). SEM path analysis was applied to test the hypotheses. The study found that digital knowledge, experience, awareness, and skill significantly impact the financial behavior of the Nepalese youth. Thus, the findings indicated that Nepalese youth who possess greater digital knowledge, exhibit positive financial behavior and have strong digital awareness are more inclined to make well-informed and advantageous financial decisions. However, the findings also indicate that digital awareness and digital skill do not influence the financial behavior of the Nepalese youth. This study could potentially contribute to academic discourse on behavioral finance and digital financial literacy, offering empirical evidence tailored to the Nepalese context. Future research can broaden their scope by examining additional variables such as personality traits, emotional intelligence, behavioral biases, and their relationships among the Nepalese youth.